Kreativitas Guru Kelas dalam Mengatasi Kesulitan Belajar Siswa - Aqlisty Nia Chandra; Izza Lailatus Sa'adah (Sekolah Tinggi Agama Islam Pati, 2022)
This study aims to determine the creativity of classroom teachers in overcoming the learning difficulties of first graders at Islamic Elementary Scool Khoiriyah Sitiluhur and to determine the inhibiting and supporting factors. This type of research is a field research with a descriptive qualitative approach. Methods of data collection use interviews, documentation, and observation. The analysis used is data reduction, data presentation, and conclusions. The results of this study are as follows: (1) the creativity of classroom teachers in learning to overcome learning difficulties experienced by first grade students at MI Khoiriyah is by using variations of learning methods, variations of learning media and having the ability to manage classes; 2) inhibiting factors include students who are super active at their age who still like to play or seek attention, students' moods are changing and some students have problems with their families and a bad playing environment; while the supporting factors include adequate facilities and infrastructure, active, creative and patient teachers and the support of families and communities in the surrounding environment.